FACTORIAL ANALYSIS OF ZINC SERUM LEVELS, FATTY ACIDS, OXIDATIVE STRESS PARAMETERS AND SUPPLEMENTATION ON ASSISTED REPRODUCTIVE TECHNOLOGY OUTCOME - Veselinovic, Aleksandra; Kotur-Stevuljević, Jelena; Stojsavljević, Aleksandar; Bojović-Jović, Dragana; Arsić, Aleksandra; Paunović, Marija; Vučić, Vesna (Journal of Medical Biochemistry, 2025)
Background: Infertility remains a prevalent global reproductive challenge significantly affecting the lives of couples worldwide. The etiology of infertility can be affected by various factors that exhibit possible relationships with one another’s. The aim of the study was to investigate factors that can interact and influence the pregnancy outcome in couples undergoing assisted reproductive technology procedure.Methods: This retrospective study included 64 couples (64 men and their female partners) undergoing assisted reproductive technology procedure, having different pregnancy outcomes and lifestyle habits. Biomarkers of antioxidative and fatty acids status in serum of both male and female partners, as well as the concentration of Zinc in serum and seminal plasma of men; and their impact on assisted reproductive technology outcome were examined.Results: We grouped the parameters using principal component analysis and identified the three most contributing factors to the pregnancy achievement – seminogram parameters in males and redox status scores in female participants; supplementation with vitamin D, magnesium, and zinc; and serum levels of omega-3 and omega-6 fatty acids.Conclusion: The study concluded that seminogram parameters, intake of micronutrients and levels of Zinc and omega-3 and omega-6 fatty acids are contributing factors to assisted reproductive technology success. Further studies on a larger cohort are needed to confirm the predictive role of these factors on the success of assisted reproductive technology.
Keywords: Keywords: assisted reproduction, fatty acids, oxidative stress, zinc